Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10943-016-0209-8
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Deliverance Phenomenon: Penteco/Charismatic Vista

Abstract: This article reflects on the deliverance concept within Classical Pentecostalism and Neo-Pentecostalism against historical and contemporary considerations. The research design combined ethnography and case study. Participant observation and in-depth interviews were used for data collection. Findings include: overstretched demonic mentality; the notion that the Penteco/Charismatic believer cannot be possessed but could be harassed by demons; and dehumanizing situations inherent in deliverance practice. It is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Asamoah-Gyadu (2015:24) explains that when medical diagnosis and treatment fails, Pentecostals are quick to interpret the ailment or any sickness as being caused by a spiritual problem, which will then call for divine healing. Hence, there is a strong element of the supernatural in Pentecostalism for both the diagnosis and the healing of diseases (Asamoah-Gyadu 2016:1646. This type of healing according to Haustein (2011:538) includes 'words of knowledge describing the presence of people with medical or psychological symptoms of possessions, such as headaches, excessive worries, or lack of sleep'.…”
Section: The Traditional Practices Of Deliverancementioning
confidence: 99%
“…Asamoah-Gyadu (2015:24) explains that when medical diagnosis and treatment fails, Pentecostals are quick to interpret the ailment or any sickness as being caused by a spiritual problem, which will then call for divine healing. Hence, there is a strong element of the supernatural in Pentecostalism for both the diagnosis and the healing of diseases (Asamoah-Gyadu 2016:1646. This type of healing according to Haustein (2011:538) includes 'words of knowledge describing the presence of people with medical or psychological symptoms of possessions, such as headaches, excessive worries, or lack of sleep'.…”
Section: The Traditional Practices Of Deliverancementioning
confidence: 99%
“…Subsequently, the means by which they contribute in mental healthcare delivery is by casting out the demons underlining the illness, providing material support and health education to their patients. Asamoah (2016) employing interview and participant observation strategies as well as case study and ethnography designs, conducted a study into the 'deliverance' concept within Classical Pentecostalism and Neo-Pentecostalism against historical and contemporary considerations. He found that, churches play much role in contributing to mental healthcare delivery in the health industry.…”
Section: Religious Faith Healers and Mental Healthcare Deliverymentioning
confidence: 99%
“…By way of illustration, research has shown that the extent to which religious leaders endorse secular intervention seems to be associated with the help-seeking behaviours of their congregations ( Cook and Hamley, 2020 ). This is important since whilst seeking religious social support may be helpful for some individuals, encouraging others with mental health difficulties to pursue exclusively spiritual interventions may be ineffective and at worse detrimental ( Mercer, 2013 ; Asamoah, 2016 ). For example, encouraging evangelical Christians with mental health concerns to engage in frequent prayer as a form of treatment has the potential to prolong their distress if evidence-based interventions are not pursued in a timely manner ( Keefe and Curtin, 2013 ; Lloyd, 2021a ).…”
Section: Introductionmentioning
confidence: 99%